Impact of Thermal Weathering on Mercury's Reflectance - O. Barraud; S. Besse; M. D’Amore; J. Helbert (Geophysical Research Letters)
Abstract MErcury Surface, Space ENviroment, GEochemistry, and Ranging (MESSENGER) observations suggest that sulfur‐bearing minerals are key components of Mercury's surface. These minerals have been proposed to explain the strong concave downward curvature between 300 and 600 nm in MESSENGER reflectance spectra of the hollows. We investigated the spectral curvature of the entire surface of Mercury and its relationship with surface temperature. High spectral curvatures map the youngest terrains: hollows, bright spots and very bright craters within the Mercury cold poles. These results demonstrate that freshly exposed materials are spectrally similar to hollows‐forming material and sulfides. High spectral curvature is muted by thermal processing near Mercury's hot poles. The optical effect of thermal weathering that we observed on Mercury are consistent with laboratory measurements on weathered CaS and includes a flattening of the reflectance in the visible. This suggests Mercury's crustal composition to be rich in sulfur‐bearing minerals.